Triple Play Services in XG-PON Network. - Horváth, T. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
This paper focuses on Triple Play services in XG-PON networks and their implementation and analysis in NS-3. Nowadays, Triple Play services dominate copper/optical networks. The network simulator allowed simulation of Passive Optical Networks (PON), especially XG-PON. Each service in the XG-PON simulation is represented OnOff application with different parameters. This article describes implementation and analysis of these services in basic topology of the XG-PON network.
Keywords: XG-PON; Triple Play; NS-3